Rural Organizing, Institutionalization, and “Getting Back”: An Interview with #RedForEd Organizer Vanessa Arredondo - Karvelis, Noah (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2022)
This interview takes place between two Arizona RedForEd movement leaders. The conversation centers primarily upon how Vanessa Arredondo, a central leader in the movement, understands the elements of rural organizing in Arizona. As the interview progresses, increased focus is placed upon the issue of institutionalization and movement engagement with electoral politics. Ultimately, the interview offers insights developed from grassroots organizing for activists and scholars interested in understanding the often-overlooked dimensions of rural organizing, as well as how they relate to issues of institutionalization and the consequent decrease of political capital.